Dietary nitrate supplementation: effects on plasma nitrite and pulmonary O2 uptake dynamics during exercise in hypoxia and normoxia - Kelly, James; Vanhatalo, Anni; Bailey, Stephen J; Wylie, Lee J; Tucker, Christopher; List, Stephen; Winyard, Paul G; Jones, Andrew M (American journal of physiology. Regulatory, integrative and comparative physiology, 2014)
We investigated the effects of dietary nitrate (NO3 (-)) supplementation on the concentration of plasma nitrite ([NO2 (-)]), oxygen uptake (V̇o2) kinetics, and exercise tolerance in normoxia (N) and hypoxia (H). In a double-blind, crossover study, 12 healthy subjects completed cycle exercise tests, twice in N (20.9% O2) and twice in H (13.1% O2). Subjects ingested either 140 ml/day of NO3 (-)-rich beetroot juice (8.4 mmol NO3; BR) or NO3 (-)-depleted beetroot juice (PL) for 3 days prior to moderate-intensity and severe-intensity exercise tests in H and N. Preexercise plasma [NO2 (-)] was significantly elevated in H-BR and N-BR compared with H-PL (P < 0.01) and N-PL (P < 0.01). The rate of decline in plasma [NO2 (-)] was greater during severe-intensity exercise in H-BR [-30 ± 22 nM/min, 95% confidence interval (CI); -44, -16] compared with H-PL (-7 ± 10 nM/min, 95% CI; -13, -1; P < 0.01) and in N-BR (-26 ± 19 nM/min, 95% CI; -38, -14) compared with N-PL (-1 ± 6 nM/min, 95% CI; -5, 2; P < 0.01). During moderate-intensity exercise, steady-state pulmonary V̇o2 was lower in H-BR (1.91 ± 0.28 l/min, 95% CI; 1.77, 2.13) compared with H-PL (2.05 ± 0.25 l/min, 95% CI; 1.93, 2.26; P = 0.02), and V̇o2 kinetics was faster in H-BR (τ: 24 ± 13 s, 95% CI; 15, 32) compared with H-PL (31 ± 11 s, 95% CI; 23, 38; P = 0.04). NO3 (-) supplementation had no significant effect on V̇o2 kinetics during severe-intensity exercise in hypoxia, or during moderate-intensity or severe-intensity exercise in normoxia. Tolerance to severe-intensity exercise was improved by NO3 (-) in hypoxia (H-PL: 197 ± 28; 95% CI; 173, 220 vs. H-BR: 214 ± 43 s, 95% CI; 177, 249; P = 0.04) but not normoxia. The metabolism of NO2 (-) during exercise is altered by NO3 (-) supplementation, exercise, and to a lesser extent, hypoxia. In hypoxia, NO3 (-) supplementation enhances V̇o2 kinetics during moderate-intensity exercise and improves severe-intensity exercise tolerance. These findings may have important implications for individuals exercising at altitude.